Penerapan Sumber Daya Manusia Dalam Meningkatkan Motivasi Kerja ASN - Aisyah Aisyah; Nur Maria Magdalena; Steviana Br Sihombing; Ella Afnira (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to explore the application of human resource management (HRM) strategies in improving the work motivation of the State Civil Apparatus (ASN). ASN work motivation is a critical factor that affects the performance of government organizations, the efficiency of public services, and the achievement of national strategic goals. In this context, various aspects of HR management such as recruitment, training and development, performance appraisal systems, and provision of incentives and rewards are identified as key factors that can increase ASN work motivation. This research methodology uses a qualitative approach through literature studies. The results showed that transparent and meritocracy-based recruitment, continuous training, and a fair and objective performance appraisal system are very influential in increasing ASN work motivation. In addition, the provision of appropriate incentives and rewards for work achievements has also proven effective in encouraging ASN enthusiasm and productivity. This study also revealed that a conducive work environment and inspirational leadership play an important role in building ASN's intrinsic motivation. The conclusion of this study confirms that strategic and integrated HR management is key to improving ASN work motivation, which in turn will contribute to improving the quality of public services and the effectiveness of government organizations. Practical recommendations from this study include the implementation of more inclusive HR policies, development of training programs relevant to ASN needs, and improvement of performance-based reward and incentive mechanisms. This research provides valuable insights for policymakers and HR managers in an effort to strengthen ASN motivation and performance in Indonesia.